Real-practice thromboprophylaxis in atrial fibrillation - Deambrosis Paola; Bettiol Alessandra; Bolcato Jenny; Pirolo Roberta; Franchin Giulia; Themistoclakis Sakis; Pellizzari Michele; Chinellato Alessandro; Giusti Pietro (Acta Pharmaceutica)
This retrospective observational study was based on databases of the Local Health Authority of Treviso, Italy. It evaluated the prevalence and the effectiveness of oral anticoagulation treatment (OAT) for the management of nonvalvular atrial fibrillation (NVAF) in everyday clinical practice. Out of 6,138 NVAF patients, only 3,024 received vitamin K antagonist (VKA). Potential barriers decreasing the probability of being treated with VKA were female sex, older age, antiplatelet treatment and history of bleeding. In addition, VKA-treatment was not in line with current ESC and AIAC guidelines, since the patients at high or low risk of stroke were under- or over-treated, resp. Among VKAtreated patients, 73 % of subjects were not at target with anticoagulation. OAT resulted to be effective in reducing stroke risk. However, stroke events were significantly influenced also by previous stroke or transient ischemic attack (hazard ratio, HR = 2.99, p < 0.001) and by previous bleeding events (HR = 1.60, p < 0.001).